Late-stage deuteration of 13C-enriched substrates for T1 prolongation in hyperpolarized 13C MRI. Issue 41 (4th May 2018) - Taglang, Céline; Korenchan, David E.; von Morze, Cornelius; Yu, Justin; Najac, Chloé; Wang, Sinan; Blecha, Joseph E.; Subramaniam, Sukumar; Bok, Robert; VanBrocklin, Henry F.; Vigneron, Daniel B.; Ronen, Sabrina M.; et al.
Abstract : Deuteration on 13 C-enriched substrates led to increases in T 1, yielding improvements in imaging parameters. Abstract : A robust and selective late-stage deuteration methodology was applied to 13 C-enriched amino and alpha hydroxy acids to increase spin–lattice relaxation constant T 1 for hyperpolarized 13 C magnetic resonance imaging. For the five substrates with 13 C-labeling on the C1-position ([1- 13 C]alanine, [1- 13 C]serine, [1- 13 C]lactate, [1- 13 C]glycine, and [1- 13 C]valine), significant increase of their T 1 was observed at 3 T with deuterium labeling (+26%, 22%, +16%, +25% and +29%, respectively). Remarkably, in the case of [2- 13 C]alanine, [2- 13 C]serine and [2- 13 C]lactate, deuterium labeling led to a greater than four fold increase in T 1 . [1- 13 C, 2- 2 H]alanine, produced using this method, was applied to in vitro enzyme assays with alanine aminotransferase, demonstrating a kinetic isotope effect.